EU-wide (regional and farm level) effects of premium decoupling and harmonisation following the health check reform; EU-weite (Regional- und Betriebsgruppen-) Effekte durch Pram̈ienentkopplung und -harmonisierung in Folge der Health-Check-Reform - Wolfgang Britz; Alexander Gocht; Ignacio Peŕez Domińguez; Torbjor̈n Jansson; Stephanie-Carolin Grosche; Na Zhao (German Journal of Agricultural Economics (GJAE), 2012)
This article investigates the income effects of decoupled payments distributed at the farm-type or uniformly at the regional level within the European Union. The analysis was conducted using detailed information on the implementation of the Health Check policy package for agricultural activities in each of the 27 member states, which is included in the Common Agricultural Policy Regionalised Impact (CAPRI) model. In the simulation experiments, the transition from individual to uniform per-hectare rates at the country level was explicitly modelled. The results show significant income shifts only for single products, such as durum wheat. Moreover, income was redistributed away from traditional "Grandes Cultures" crop production to fodder production, an effect primarily caused by the capitalisation of decoupled premiums on previously unsubsidised land. Cattle, sheep and goat production was primarily affected in the animal sector. Land values are expected to increase considerably, especially those of grasslands.
Keywords: 330